2017
DOI: 10.1183/13993003.01486-2016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sleep disordered breathing on short-term post-operative outcome after elective coronary artery bypass graft surgery: a prospective observational study

Abstract: Sleep disordered breathing (SDB) is common in patients with coronary disease, but its impact on post-operative recovery after coronary artery bypass graft surgery (CABG) is unclear. We therefore determined the effects of SDB on post-operative outcome after elective CABG.In this prospective two-centre study, 219 patients due to receive elective CABG underwent cardiorespiratory polygraphy for SDB prior to surgery and were monitored for post-operative complications. The primary end-point was a composite of 30-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…Another question of great clinical interest is whether treatment with continuous positive airway pressure (CPAP) in the subgroup of patients with excessive SDB prior to surgery (in this case CABG) would help protect them against post-operative infections, as posited by the authors of the present study (although they did not carry out such analysis) [5]. Although it is true that CPAP has been shown to decrease some systemic inflammatory markers [18] and could be an effective treatment in the perioperative period [19], its protective capacity is likely to be less than expected if the results of RUPPRECHT et al [5] are confirmed.…”
mentioning
confidence: 41%
See 3 more Smart Citations
“…Another question of great clinical interest is whether treatment with continuous positive airway pressure (CPAP) in the subgroup of patients with excessive SDB prior to surgery (in this case CABG) would help protect them against post-operative infections, as posited by the authors of the present study (although they did not carry out such analysis) [5]. Although it is true that CPAP has been shown to decrease some systemic inflammatory markers [18] and could be an effective treatment in the perioperative period [19], its protective capacity is likely to be less than expected if the results of RUPPRECHT et al [5] are confirmed.…”
mentioning
confidence: 41%
“…Although it is true that CPAP has been shown to decrease some systemic inflammatory markers [18] and could be an effective treatment in the perioperative period [19], its protective capacity is likely to be less than expected if the results of RUPPRECHT et al [5] are confirmed. This is because, on the one hand, the significant number of patients with central SA would theoretically limit the action of CPAP (an evaluation of the effect of adaptive servoventilation in this subgroup of patients would be an interesting research topic), while on the other hand, as has already been made evident by other studies, CPAP or noninvasive ventilation treatments in patients under sedation with a higher risk of infections (i.e.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…The sympathetic activation, blood pressure surges, and hypercoagulability caused by sleep apnea have been postulated as mediators of an increased cardiovascular risk [11]. Numerous studies have demonstrated the associations of sleep apnea with various short-and long-term complications after CABG, including new-onset atrial brillation, respiratory complications, hospital readmission, and major adverse cardiac and cerebrovascular events (MACCEs) [12][13][14][15]. These ndings were corroborated by the recently published results of the SABOT (Sleep Apnea and Bypass Operation) study, which revealed an association of sleep apnea with a 1.57-fold increase in the risk of developing MACCEs [16].…”
Section: Introductionmentioning
confidence: 99%